The Effects of Delays by Accounting Policy-Setters in Reconciling the Accounting Treatment of Stock Options and Stock Appreciation Rights. - Stickney, Clyde P.; Wallace, Wanda A. (The Accounting Review, 1984)
Abstract ABSTRACT: This research investigates the effects of delays by accounting policy-setters in reconciling the accounting treatment of stock options and stock appreciation rights (SARs). Comment letters to the FASB concerning Interpretation No. 28, observed SAR adoption practices, direct survey results from companies not adopting SARs, stock prices' reaction to the related accounting policy process, and the structure of SAR plans are analyzed. Analysis of the content of lobbyists' letters, descriptive statistics, t-tests, correlation coefficients, and an event study of related AICPA and FASB announcements are utilized. The evidence supports the hypotheses that the accounting treatment of SARs has deterred companies with stock option plans from adopting SARs, has deterred smaller companies from adopting SARs to a greater extent than it has deterred larger companies, has had a discernible "bad news" effect on the market, and has affected the form of those SAR plans which have been adopted. The recent advent of so-called "stock depreciation rights" may well lead to the elimination of SARs, largely due to the accounting treatment of SARs.